(untitled) (Research, Society and Development, 2020)
Zooliterature focuses on the study of works that contain animals. Two literary books, Black Beauty, by Anna Sewell, and Michael Morporgo, by War Horse, present enough elements to be classified as zooliterature. These two romances were read in order to verify the emotions of the equine protagonists to be compared with the of the scientific literature, and verify if they are related to the reality, considering the human factor and the affective states of the animal characters. Thus, parts of the texts were selected for the study and then interpreted. In this study, the precept that the way people acts towards to horses and their attitudes result in an emotional valance in animals with proportional consequences in their quality of life. Although some feelings and emotions found in equine characters are anthropomorphic or others are not yet recognized by science, they can promote reflections and create empathy for horses in the readers of these two books.